Whey protein improves glycemia during an oral glucose tolerance test compared to vigorous-intensity aerobic exercise in young adult men - Ryan A. Gordon; Emily L. Zumbro; Todd J. Castleberry; Matthew L. Sokoloski; Matthew F. Brisebois; Christopher J. Irvine; Anthony A. Duplanty; Vic Ben-Ezra (BMC, 2022)
Abstract Background Both aerobic exercise and whey protein can improve glucose regulation. The purpose of this study was to investigate how a single bout of vigorous-intensity aerobic exercise and whey protein, independently, as well as when combined, influence glycemia during an oral glucose tolerance test in sedentary, young men. Methods Healthy males (n = 11) completed four randomized trials: no exercise/no whey protein (R); exercise (EX; walking at 70% VO2max for 60 min); 50 g of whey protein (W); and exercise combined with 50 g of whey protein (EXW). Each trial included a 75 g oral glucose tolerance test (OGTT) that was completed after an overnight fast. Blood samples were collected over a two-hour period during the OGTT. For EX and EXW, the exercise was performed the evening before the OGTT and the 50 g of whey protein was dissolved in 250 mL of water and was consumed as a preload 30 min prior to the OGTT. For R and EX, participants consumed 250 mL of water prior to the OGTT. Plasma samples were analyzed for glucose, insulin, C-peptide, glucagon, gastric inhibitory peptide (GIP) and glucagon like peptide 1 (GLP-1), and postprandial incremental area under the curve (iAUC) was calculated for each. Results Glucose iAUC was reduced during W (− 32.9 ± 22.3 mmol/L) compared to R (122.7 ± 29.8 mmol/L; p < 0.01) and EX (154.3 ± 29.2 mmol/L; p < 0.01). Similarly, glucose iAUC was reduced for EXW (17.4 ± 28.9 mmol/L) compared to R and EX (p < 0.01 for both). There were no differences in iAUC for insulin, C-peptide, GIP, GLP-1, and glucagon between the four trials. Insulin, C-peptide, glucagon, GIP, and GLP-1 were elevated during the whey protein preload period for W and EXW compared to EX and R (p < 0.01). There were no differences for insulin, C-peptide, glucagon, GIP, or GLP-1 between trials for the remaining duration of the OGTT. Conclusions Glucose responses during an oral glucose tolerance test were improved for W compared to EX. There were no additional improvements in glucose responses when vigorous-intensity aerobic exercise was combined with whey protein (EXW).